Plugged in and charging: Environmentalism Factors Does Affect Behavioral Intention to Purchase Electric Cars in Indonesia, But Non-Environmental Factors are Important Too - Salsabila, Hana; Salehudin, Imam (Smart City, 2023)
The adoption of electric cars is considered a solution for promoting energy conservation and reducing air pollution. However, electric car purchasing in developing countries is currently at a nascent stage. More research is required to see if environmental factors do matter in the consumer's decision to purchase an electric car. This study aims to examine the relationship between environmental factors and behavioral intention to purchase electric cars in Indonesia. The study recruited 300 respondents from five major areas of Java Island who are aware of electric cars but currently owned only non-electric cars. The study integrated the theory of planned behavior and the norm activation model to analyze the data. The findings suggest that perceived behavioral control plays a key role in mediating the effect of environmental factors on the intention to purchase electric cars. The awareness of consequences and ascription of responsibility also influence personal norms which affect the purchase intention. The study concludes that environmentalism factors do contribute to the purchase intention of electric cars, but it is mediated by perceived behavioral control. Additionally, non-environmental factors such as affordability and convenience also play a crucial role.